Determinants of Planned Behavior as Predictors of Tobacco and Alcohol Consumption in adolescents - Lopez-Cisneros, Manuel Antonio; Alonso Castillo, María Magdalena (Horizonte Sanitario, 2022)
Objective: know the effect of the determinants of planned behavior on tobacco and alcohol consumption in adolescents high schools.Material and Methods: A predictive correlational descriptive study was carried out with 735 adolescents from High school in the State of Nuevo León, Mexico. A self-administered questionnaire was used, which includes concerning sociodemographic variables, tobacco and alcohol consumption, attitude, subjective norm and perceived behavioral control towards tobacco and alcohol consumption. Logistic regression models were carried out of attitude, subjective norm, perceived behavioral control on tobacco and alcohol consumption.Results: The subjective norm (OR = 1.02, p = .028) and the perceived behavioral control (OR = 1.084, p = .001) were showed significant for predicting tobacco consumption ever in life. While attitude (OR = .980, p = .017), subjective norm (OR = 1.034, p = .025) and perceived behavioral control (OR = 1.080, p = .001) were showed significant for predicting alcohol consumption ever in life.Conclusions: With based on the results, it is possible to determine the usefulness and relevance of the theory of planned behavior and the generation of new scientific knowledges that allows the design of programs to face the situations that adolescents perceive as facilitators of tobacco and alcohol consumption.Keywords: Adolescent; Alcohol drinking; Tobacco consumption; Attitude; Social norms.